Identification and characterisation of a small marker chromosome using non-isotopic in situ hybridisation with X and Y specific probes. Issue 3 (March 1989) - Crolla, J A; Smith, M; Docherty, Z
Abstract : A 13 year old male with mild mental retardation, obesity, and poor secondary sexual differentiation was found to have a 46, X, +, mar karyotype. In situ hybridisation with X and Y specific probes proved the marker to be composed of Y centromeric and short arm material.